Effective routing protocol for wireless sensor networks using CRT-leach algorithm / Kamaldeen Ayodele Raji, Ayisat Wuraola Asaju-Gbolagade and Kazeem Alagbe Gbolagade - Ayodele Raji, Kamaldeen; Asaju-Gbolagade, Ayisat Wuraola; Gbolagade, Kazeem Alagbe (Universiti Teknologi MARA, 2021)
Wireless Sensor Networks (WSNs) consist of huge number of sensor nodes dispersed in a domain of enthusiasm with at least one sink for watching the environment and physical situation. These sensor hubs are circulated in threatening conditions and are unprotected to deficiencies, for example, power dissemination, equipment glitches, communication link errors and malicious attacks, among others. It has been established that essentialness, speed and unwavering quality are the chief test in the usefulness of WSNs as they are controlled with compelled imperativeness and restricted equipment assets. Accordingly, it is necessary to structure vitality proficient steering conventions for WSNs applications. Chinese Remainder Theorem (CRT)- based packet splitting integrated with Low-Energy Adaptive Clustering Hierarchy (LEACH) algorithm routing protocol was proposed so as to decrease vitality utilization during correspondence and improve message dependability in WSNs. The consequences of exploratory reproductions show that the proposed structure delivered powerful directing convention for WSNs when contrasted with existing routing protocols to the extent essentialness usage, speed, equipment necessities and transformation delay continuously WSNs.